RXRα Positively Regulates Expression of the Chicken PLIN1 Gene in a PPARγ-Independent Manner and Promotes Adipogenesis - Sun, Yuhang; Zhai, Guiying; Li, Rui; Zhou, Weinan; Li, Yumao; Cao, Zhiping; Wang, Ning; Li, Hui; Wang, Yuxiang (Frontiers in Cell and Developmental Biology, 2020)
Perilipin1 (PLIN1), the most abundant lipid droplet (LD)-associated protein, plays a vital role in regulating lipid storage and breakdown in adipocytes. Recently, we found that the overexpression of PLIN1 promotes chicken preadipocyte lipid accumulation. However, the mechanisms by which transcription of the chicken PLIN1 gene is regulated remain unknown. In this study, we investigated the role of retinoid X receptor α (RXRα) in transcription of the chicken PLIN1 gene. Notably, reporter gene and expression assays showed that RXRα activates transcription of the chicken PLIN1 gene in a PPARγ-independent manner. Furthermore, promoter deletion and electrophoretic mobility shift assay (EMSA) analysis revealed that the chicken PLIN1 gene promoter region (-774/-785) contains an RXRα-binding site. Further study demonstrated that RXRα overexpression promotes differentiation of an immortalized chicken preadipocyte cell line (ICP1), causing a concomitant increase in PLIN1 transcripts. Taken together, our results show for the first time that RXRα activates transcription of the chicken PLIN1 gene in a PPARγ-independent manner, which might be at least in part responsible for RXRα-induced adipogenesis.